Inflation Dynamics in the New EU Member States: How Relevant Are External Factors? - Alexander Mihailov; Fabio Rumler; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2009)
In this paper we evaluate the relative influence of external versus domestic inflation drivers in the 12 new European Union (EU) member countries. Our empirical analysis is based on the New Keynesian Phillips Curve (NKPC) derived in Galí and Monacelli (2005) for small open economies (SOE). Employing the Generalized Method of Moments (GMM), we find that the SOE NKPC is well supported in the new EU member states. We also find that the inflation process is dominated by domestic variables in the larger countries of our sample, whereas external variables are mostly relevant in the smaller countries.
Keywords: C32; C52; E31; F41; P22; 330; New Keynesian Phillips Curve; small open economies; inflation dynamics; new EU member countries; GMM estimation; Inflation; New-Keynesian Phillips Curve; Kleines-offenes-Land; Momentenmethode; Schätzung; EU-Staaten (Osteuropa)